Energy-Performance Evaluation with Revit Analysis of Mathematical-Model-Based Optimal Insulation Thickness - Balo, Figen; Ulutas, Alptekin (Mdpi, 2023)
This study investigates the optimum insulation thickness value using MATLAB Optimization Toolbox based on a mathematical model for sandwich walls that are formed with different insulation-building materials by different fuel types for a particular city located in the second climatic region of Turkey. In the second stage of study, using the BIM-based Revit simulation program, a building was designed with the same building-insulation materials under the same climate conditions. The six different wall performances were compared for the designed building. The study proposes a comprehensive approach by combining technical and economic factors in the sustainable design of buildings. The computational results indicate that using different energy alternatives has a significant impact on the air quality in residential areas. The lowest value is reached when natural gas is used. The energy cost savings change from 7.56 to 14.12 TRY/m(2) for external walls. While payback periods vary between 2.15 and 3.76 years for external walls, the lowest period for all wall types is obtained for electricity, which has a high cost. The optimum insulation thickness for 10 years of lifetime varies between 0.02 and 0.16 m. This study reflects that the highest optimal insulating thickness is reached when electricity is utilized as the energy source for all wall types. According to the Revit analysis, the lowest energy consumption of 21,677 kWh during one year using natural gas was obtained for a building material of porous light brick and an insulation material of glass wool.
Keywords: optimum insulation thickness; energy efficiency; environmental impact